ANALYSIS OF THE IMPLEMENTATION OF THE HOSPITAL HEALTH PROMOTION PROGRAM (PKRS) AT ISLAMIC HOSPITALS IN THE MEDAN CITY REGION - Tria Astrid Nabila Harahap; Adillah Maharani Tanjung; Rizka Octavia; Nadia Hafifah Siregar; Nur Wanny; Dilla Rahmayanti Siregar; Eliska Eliska (HEARTY, 2026)
This study aims to analyze the implementation of the Hospital Health Promotion Program (PKRS) at an Islamic Hospital in Medan City. PKRS is an activity that focuses on promotive and preventive efforts to increase awareness, knowledge, and community participation in maintaining and improving health. This study used a qualitative descriptive method with data collection techniques through in-depth interviews, observation, and documentation of PKRS officers. The results of the study indicate that the implementation of PKRS is carried out through two main approaches, namely direct and indirect promotion. Direct promotion is carried out through counseling activities, health lectures, and visits to various agencies, while indirect promotion is carried out through social media such as Instagram and Facebook to disseminate health information. Evaluation of activities is carried out routinely through activity reports, medical record data, and patient visits. The results of the study concluded that the implementation of PKRS at an Islamic Hospital in Medan City has been effective, supporting the improvement of service quality, and contributing to the achievement of hospital accreditation. This program also strengthens the positive image of the hospital as an institution oriented towards promotive and preventive efforts in health services.